Tsudaea, a new genus of Brachycentridae (Trichoptera) from Japan - Nozaki, Takao (Zootaxa, 2009)
The species, previously known as "Eobrachycentrus kitayamanus (Tsuda 1942)" originally described based on a male specimen, is here associated with the larval stage described by Akagi (1962) as "Micrasema sp. MD". Because both the adult and larva of this species have many unique characters within the family Brachycentridae, a new genus, Tsudaea, is erected for this species. Descriptions and illustrations of the adult and immature stages of Tsudaea kitayamana are provided. The larvae of T. kitayamana are unique among the Brachycentridae in having lateral humps present on the first abdominal segment.